Metronomic photodynamic therapy using an implantable LED device and orally administered 5-aminolevulinic acid - Izumi Kirino (Nature Portfolio, 2020)
Abstract Metronomic photodynamic therapy (mPDT) is a form of PDT that induces cancer cell death by intermittent continuous irradiation with a relatively weak power of light for a long duration (several days). We previously developed a wirelessly powered, fully implantable LED device and reported a significant anti-tumor effect of mPDT. Considering application in clinical practice, the method used for repeated administrations of photosensitizers required for mPDT should not have a high patient burden such as the burden of transvenous administration. Therefore, in this study, we selected 5-aminolevulinic acid (ALA), which can be administered orally, as a photosensitizer, and we studied the antitumor effects of mPDT. In mice with intradermal tumors that were orally administered ALA (200 mg/kg daily for 5 days), the tumor in each mouse was simultaneously irradiated (8 h/day for 5 days) using a wirelessly powered implantable green LED device (532 nm, 0.05 mW). Tumor growth in the mPDT-treated mice was suppressed by about half compared to that in untreated mice. The results showed that mPDT using the wirelessly powered implantable LED device exerted an antitumor effect even with the use of orally administered ALA, and this treatment scheme can reduce the burden of photosensitizer administration for a patient.